The Subcutaneous sarcoidosis on the digits: Subcutaneous sarcoidosis - Norikawa, Natsumi; Yamamoto, Toshiyuki (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
A 47-year old female developed subcutaneous nodules on the first to third digits and increased the number. Physical examination showed that multiple subcutaneous nodules were found on the first to third digits of her dominant hand (right hand), as well as both forearms and lower legs. Histological examination showed non-caseating epithelioid cell granulomas in the lower dermis to subcutis with multinucleated giant cells. Subcutaneous sarcoidosis is occasionally observed. However, cases of subcutaneous sarcoidosis occurring on the digits are rare. The present case developed subcutaneous nodules on the right hand (dominant hand), which may suggest Koebner’s phenomenon.